2012
DOI: 10.1016/j.ijrobp.2010.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Proton Radiotherapy for Parameningeal Rhabdomyosarcoma: Clinical Outcomes and Late Effects

Abstract: Purpose To report the clinical outcome and late side effect profile of proton radiotherapy in the treatment of children with parameningeal rhabdomyosarcoma (PM-RMS). Methods and Materials Seventeen consecutive children with PM-RMS were treated with proton radiotherapy at Massachusetts General Hospital between 1996 and 2005. We reviewed the medical records of all patients and asked referring physicians to report specific side effects of interest. Results Median patient age at diagnosis was 3.4 years (range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 21 publications
(42 reference statements)
5
94
0
2
Order By: Relevance
“…Studies of tumours outside the cns-including skull base chordoma and chondrosarcoma 22,23 , uveal melanoma 23,24 , germ-cell tumours 25 , high-risk neuroblastoma 26,27 , parameningeal rhabdomyosarcoma 28 , bladder and prostate rhabdomyosarcoma 29 , other soft tissue sarcomas 30 , Ewing sarcoma 31 , and mediastinal Hodgkin lymphoma 32 -uniformly showed that pbt is well tolerated, with local control rates similar to or higher than those achieved with photon rt. Although planning studies and early clinical results are promising, long-term data supporting a clear advantage of pbt over photon rt are not yet available.…”
Section: Pediatricsmentioning
confidence: 99%
“…Studies of tumours outside the cns-including skull base chordoma and chondrosarcoma 22,23 , uveal melanoma 23,24 , germ-cell tumours 25 , high-risk neuroblastoma 26,27 , parameningeal rhabdomyosarcoma 28 , bladder and prostate rhabdomyosarcoma 29 , other soft tissue sarcomas 30 , Ewing sarcoma 31 , and mediastinal Hodgkin lymphoma 32 -uniformly showed that pbt is well tolerated, with local control rates similar to or higher than those achieved with photon rt. Although planning studies and early clinical results are promising, long-term data supporting a clear advantage of pbt over photon rt are not yet available.…”
Section: Pediatricsmentioning
confidence: 99%
“…Particle radiotherapy, the most common being proton radiotherapy, is currently being utilized for treatment of pediatric sarcomas. 110,111 In contrast to photons, protons and other charged particles have a discrete stopping distance that minimizes exposure of normal tissues to unnecessary radiotherapy 112 as well as allowing dose escalation and improved local control in tumors adjacent to critical structures such as the spine and skull base. 113 Second malignancy risk reduction is one of the expected long-term improvements in late effects because the radiation exposure is generally reduced by 60% to 70% in comparison to photon plans.…”
Section: New Directionsmentioning
confidence: 99%
“…Los valores de CPO que observamos fueron 1,29 para controles de LLA con tratamiento de quimioterapia y de 3,4 para otros cáncer, incluso cuando las terapias se combinaban con radioterapia que no alcanzaban valores superiores a 5,5; muy por debajo de lo que se ha estudiado a través de los años y que se describe en la literatura para los pacientes que han recibido terapia antineoplásica y que presentan promedios de hasta de 9,19. O incluso más bajos para pacientes que se encontraban en control después de la quimioterapia que mostraban valores de 4,5 y 17,01 (SD, 9,14, respectivamente) [21][22][23][24][25][26][27] . Por el contrario, en piezas temporales de los pacientes de este estudio, encontramos índices de caries más altos: 5,43 en otros cáncer y de 5,17 en LLA, en contraposición a la literatura que muestra ceo general para los pacientes que han recibido terapia antineoplásica independientemente de su modalidad 3,20,23 .…”
Section: Discussionunclassified